2009
DOI: 10.1111/j.1467-9310.2009.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and archetype users of open innovation

Abstract: Extant research on open innovation (OI) offers no systematic insight of how and why firms differ regarding the extent to which they conduct OI activities. Whereas past theoretical contributions have focused on explaining the externalisation of R&D activities as a result of firm‐external factors, we focus on explaining this externalisation as a result of firm‐internal weaknesses, specifically, impediments to innovation. Using the exploration–exploitation dichotomy as our theoretical framework, we develop hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
231
3
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(256 citation statements)
references
References 50 publications
13
231
3
9
Order By: Relevance
“…(2009) observed a trend towards open innovation across industries, but found that this trend was not continuous but composed of shocks, and that the timing between the shocks differs among various industries. Applying open innovation appears to be more a matter of business strategy than a matter of industry trends (Keupp & Gassmann, 2009), suggesting that for explaining open innovation adoption the internal environment in firms is more important than the external environment. Gassmann and Enkel (2004) identified three core open innovation processes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2009) observed a trend towards open innovation across industries, but found that this trend was not continuous but composed of shocks, and that the timing between the shocks differs among various industries. Applying open innovation appears to be more a matter of business strategy than a matter of industry trends (Keupp & Gassmann, 2009), suggesting that for explaining open innovation adoption the internal environment in firms is more important than the external environment. Gassmann and Enkel (2004) identified three core open innovation processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because of having missed data, 9 questionnaires were eliminated. Bianchi et al, 2011;Chesbrough, 2002;Granstrand, 2004 Acquisition of other firm Gassmann & Enkel, 2004;Harison & Koski, 2010 Granstrand, 2004;Lord et al, 2002;Steensma & Corley, 2000;Von Hippel, 2005 Licensing in Chiaroni et al, 2010;Granstrand, 2004Outsourcing R&D contract Chiaroni et al, 2010Granstrand, 2004;Steensma & Corley, 2000 Technology Scanning Chesbrough, 2002;Chiaroni et al, 2010;Keupp & Gassmann, 2009;Teece, 1986 Spin offs and incubators BurgeSmani & Wheelwright, 2004;Chesbrough, 2002;Gassmann & Enkel, 2004 Divestment(123) Christensen & Overdorf, 2000; Gassmann & Enkel, 2004;Granstrand, 2004;Lee et al, 2010;Lichtenthaler, 2008;Von Hippel, 2005 Creation and selling of innovative Projects (123) Granstrand, 2004;Lichtenthaler, 2008; Outside-in Venture Capital Bianchi et al, 2011;Granstrand, 2004;Huizingh, 2011 Licensing out (123) Arora et al, 2001;Chiaroni et al, 2010;Gassmann, 2006;Gassmann & Enkel, 2004;Granstrand, 2004 Supply technical and scientific services Chiaroni et al, 2010;Gassmann, 2006;…”
Section: Methodsmentioning
confidence: 99%
“…Keupp and Gassmann (2009) identified three clusters of open companies: "professionals" collaborating both broadly and deeply, "explorers" with a medium to large breadth and a medium degree of depth, "scouts" with a medium to large breadth and a low degree of depth. Idrissia et al (2012) define "open" the companies with high breadth and depth, "user" the companies with high breadth and low depth, "interactive" the ______________________________________________________________________________________________________________ …”
Section: Literature Reviewmentioning
confidence: 99%
“…manufacturing firms search broadly when knowledge is not abundant. Similarly Keupp and Gassmann (2009) find Swiss manufacturing firms with information shortages search broadly.…”
Section: Open Innovation To Resolve Technological Interdependencementioning
confidence: 99%
“…The implication of this is that many project-based firms lack stable knowledge repositories. Similar knowledgeconstrained environments are known to induce broad search strategies (Garriga et al, 2013;Keupp & Gassmann, 2009). For instance, Garriga et al (2013) find that Spanish 6 Simon's (1962) definition of a complex system is '…one made up of a large number of parts that interact in a nonsimple way.…”
Section: Open Innovation To Resolve Technological Interdependencementioning
confidence: 99%